Ultrastable Sodium–Sulfur Batteries without Polysulfides Formation Using Slit Ultramicropore Carbon Carrier - Guo, Qiubo; Li, Shuang; Liu, Xuejun; Lu, Haochen; Chang, Xiaoqing; Zhang, Hongshen; Zhu, Xiaohui; Xia, Qiuying; Yan, Chenglin; Xia, Hui (Advanced science, 2020)
The formation of the soluble polysulfides (Na2Sn, 4 ≤ n ≤ 8) causes poor cycling performance for room temperature sodium–sulfur (RT Na–S) batteries. Moreover, the formation of insoluble polysulfides (Na2Sn, 2 ≤ n < 4) can slow down the reaction kinetics and terminate the discharge reaction before it reaches the final product. In this work, coffee residue derived activated ultramicroporous coffee carbon (ACC) material loading with small sulfur molecules (S2–4) as cathode material for RT Na–S batteries is reported. The first principle calculations indicate the space confinement of the slit ultramicropores can effectively suppress the formation of polysulfides (Na2Sn, 2 ≤ n ≤ 8). Combining with in situ UV/vis spectroscopy measurements, one‐step reaction RT Na–S batteries with Na2S as the only and final discharge product without polysulfides formation are demonstrated. As a result, the ultramicroporous carbon loaded with 40 wt% sulfur delivers a high reversible specific capacity of 1492 mAh g−1 at 0.1 C (1 C = 1675 mA g−1). When cycled at 1 C rate, the carbon–sulfur composite electrode exhibits almost no capacity fading after 2000 cycles with 100% coulombic efficiency, revealing excellent cycling stability and reversibility. The superb cycling stability and rate performance demonstrate ultramicropore confinement can be an effective strategy to develop high performance cathode for RT Na–S batteries. The coffee residue derived ultramicroporous carbon material loading with small sulfur molecules (S2–4) as cathode material for room temperature (RT) Na–S batteries can effectively suppress the formation of polysulfides (Na2Sn, 2 ≤ n ≤ 8). Due to the special reaction mechanism, the ultramicroporous carbon loaded with 40 wt% sulfur (ACC‐40S) exhibits good rate capability, low‐self discharge, and excellent cycling stability.